Organization theory management & leadership analysis - Blomberg, Jesper 1963- ([SAGE], 2023)
In Organization Theory: Management and Leadership Analysis, Jesper Blomberg explores the fields of organization theory and management, making sense of complex theories and encouraging critical thinking"--